Using a mentorship model to localise the Practical Approach to Care Kit (PACK): from South Africa to Brazil. (25th October 2018) - Wattrus, Camilla; Zepeda, Jorge; Cornick, Ruth Vania; Zonta, Ronaldo; Pacheco de Andrade, Matheus; Fairall, Lara; Georgeu-Pepper, Daniella; Anderson, Lauren; Eastman, Tracy; Bateman, Eric D; CRUZ, Alvaro A; Bachmann, Max O; et al.
Abstract : Brazil's Sistema Único de Saúde, or Unified Health System policy, has delivered major improvements in health coverage and outcomes, but challenges remain, including the rise of non-communicable diseases (NCDs) and variations in quality of care across the country. Some of these challenges may be met through the adaptation and implementation of a South African primary care strategy, the Practical Approach to Care Kit (PACK). Developed by the University of Cape Town's Knowledge Translation Unit (KTU), PACK is intended for in-country adaptation by employing a mentorship model. Using this approach, the PACK Adult guide and training materials were localised for use in Florianópolis, Santa Catarina, Brazil, as part of an initiative to reform primary care, expand care for NCDs and make services more accessible and equitable. The value of the collaboration between the KTU and Florianópolis municipality is the transfer of skills and avoidance of duplication of effort involved in de-novo guide development, while ensuring that materials are locally acceptable and applicable. The collaboration has informed the development of the KTU's PACK mentorship package and led to a relationship between the groups of developers, ensuring ongoing learning and research, with the potential of assisting the further scale-up of PACK in Brazil.